Polyclinic Geriatrics, Rumah Sakit Haji Medan, Risk Factors for Isolated Systolic Hypertension in the Elderly - Zahrah, Nadianty Az; Nasution, Huwainan Nisa (Universitas Muhammadiyah Sumatera Utara, 2022)
ABSTRACTIntroduction: Hypertension is a manifestation of hemodynamic balance disorders in the cardiovascular system. Isolated systolic hypertension was defined as systolic blood pressure ?140 mmHg and diastolic blood pressure ?90 mmHg. Objective: The purpose of this study was to analyze the effect of family history, obesity, smoking, physical activity and consumption of salt and fat on the incidence of isolated systolic hypertension in the elderly at the Geriatrics Clinic of Haji Hospital Medan. Method: The design of this study was an analytic observasional study with a case control approach using a questionnaire from patients at the Geriatrics Polyclinic, Haji Hospital Medan. The sampling technique used was purposive sampling. Results: From 90 samples, it was found that there was an effect of family history (p-value=0,003; OR=3,62; CI 95% = 1,51-8,65), smoking (p-value=0,035; OR=2,47; CI 95% = 1,05-5,76), physical activity (p-value=0,010; OR=3,07; CI 95% = 1,28-7,36), and consumption of salt and fat (p-value=0,033; OR=2,53; CI 95% = 1,07-5,98) on the incidence of isolated systolic hypertension in the elderly and there is no effect of obesity on the incidence of isolated systolic hypertension (p-value=0,827; OR=1,10; CI 95% = 0,46-2,59). The results of multivariate analysis showed that the most dominant variable influencing the incidence of isolated systolic hypertension was family history (p-value = 0,023; Exp ? =0,347). Conclusion: There is an effect of family history, smoking, physical activity, and consumption of salt and fat on the incidence of isolated systolic hypertension in the elderly and there is no influence of obesity with the incidence of isolated systolic hypertension in the elderly. The most dominant variable influencing the incidence of isolated systolic hypertension in the elderly is family history.Keyword : Elderly, Isolated Systolic Hypertension, Risk Factors